Who is using flexible work arrangements among couples? A longitudinal analysis of the disparities between gender, parenthood, and cccupations - WANG, Senhu (Institutional Knowledge at Singapore Management University, 2025)
The rise of flexible work arrangements (FWAs) holds promise for advancing gender equality by enabling both men and women to better manage work and family. However, this expectation hinges on the actual utilization of FWAs by both genders in response to family needs. Drawing on longitudinal dyadic data from the UK (2010–2022), this study examines the disparities in the use of FWAs among couples by gender, parenthood, and occupation. We find that wives' use of all types of FWAs significantly increases after parenthood, whereas husbands' use remains unchanged. Moreover, mothers' use of FWAs varies by occupation and the type of FWAs. While traditional FWAs (e.g., reduced hours arrangements) are widely used by mothers regardless of their occupations, mothers from professional occupations are more likely to use novel FWAs (e.g., flexible schedule and teleworking arrangements) than those from non-professional occupations. The workplace gender inequalities are thus likely to continue in the FWA era, albeit in more subtle and nuanced forms that vary according to the types of FWAs and occupations involved.